2021
DOI: 10.3390/ijms22041517
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Sequencing in the Preoptic Region of Rat Dams Reveals a Role of Androgen Receptor in the Control of Maternal Behavior

Abstract: (1) Background: Preoptic region of hypothalamus is responsible to control maternal behavior, which was hypothesized to be associated with gene expressional changes. (2) Methods: Transcriptome sequencing was first applied in the preoptic region of rat dams in comparison to a control group of mothers whose pups were taken away immediately after parturition and did not exhibit caring behavior 10 days later. (3) Results: Differentially expressed genes were found and validated by quantitative RT-PCR, among them NAC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 54 publications
(73 reference statements)
0
3
0
Order By: Relevance
“…With hyperandrogenism being a key feature in clinical PCOS and the basis for most preclinical animal models of the disorder, it is important to consider potential effects of elevated androgens on mammalian maternal behaviour. A recent RNA‐sequencing analysis of the MPOA of lactating rats with and without pups, showed that androgen receptor (AR) expression is downregulated in the presence of pups 65 . In that same study, central administration of an AR antagonist to rat dams increased pup‐directed behaviour, 65 suggesting that AR‐signalling in the brain suppresses normal postpartum maternal behaviour.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…With hyperandrogenism being a key feature in clinical PCOS and the basis for most preclinical animal models of the disorder, it is important to consider potential effects of elevated androgens on mammalian maternal behaviour. A recent RNA‐sequencing analysis of the MPOA of lactating rats with and without pups, showed that androgen receptor (AR) expression is downregulated in the presence of pups 65 . In that same study, central administration of an AR antagonist to rat dams increased pup‐directed behaviour, 65 suggesting that AR‐signalling in the brain suppresses normal postpartum maternal behaviour.…”
Section: Discussionmentioning
confidence: 97%
“…A recent RNA‐sequencing analysis of the MPOA of lactating rats with and without pups, showed that androgen receptor (AR) expression is downregulated in the presence of pups 65 . In that same study, central administration of an AR antagonist to rat dams increased pup‐directed behaviour, 65 suggesting that AR‐signalling in the brain suppresses normal postpartum maternal behaviour. To date, few studies have investigated the impact of androgen administration during pregnancy on subsequent maternal behaviour in mammals.…”
Section: Discussionmentioning
confidence: 97%
“… 88 In turn, AR levels were also suppressed in the MPOA of mothers. 89 In contrast, it has been observed that during parturition 90 , 91 and during lactation 92 there is an increase in OTR levels in mothers' MPOA. Furthermore, hormones can affect each other’s receptor levels, as evidenced by estrogen-induced progesterone receptor (PR) expression, 93 and progesterone’s ability to elevate prolactin receptor levels (PRLRs).…”
Section: Hormonal Influence Of Social Behaviors In the Preoptic Areamentioning
confidence: 97%